Le périple erratique de la mendiante durassienne - Ledwina, Anna (2022)
Marguerite Duras focuses on a rejected individual on the margins of society. Her literary characters oppose beingperceived as devoid of autonomy, contesting the fixed model of a submissive and passive woman. On the contrary,they reject the social order and the traditional system of values, claiming the right to freedom and thus showing/demonstrating/proving transgressive female behaviour. Duras’ heroine, a mysterious, crazy person who is lookingfor love and is aware of her otherness and alienation, appears as a kind of femme fatale or a witch. This image of a‘different’ woman – a disturbing, unhappy, lost, borderline person experiencing a specific crisis – is best illustratedby a beggar. She identifies, par excellence, with the wandering to the lands of perdition and its various meanings/readings. Her journey is, at the same time, a sign of dereliction, an attempt at liberation and a quest for identity.
Keywords: Duras, Marguerite